2012
DOI: 10.2147/opth.s33169
|View full text |Cite
|
Sign up to set email alerts
|

Ocular complications of bungee jumping

Abstract: AimIn this paper, we will try to highlight the importance of various investigations and their crucial role in identifying whether the defect is structural or functional.Case historyA 24-year-old woman presented with ocular complications after bungee jumping. Subsequently, although all ophthalmic signs resolved, she complained of decreased vision in her left eye.ConclusionInitial ophthalmic injury was detected by optical coherence tomography scan showing a neurosensory detachment of the fovea. This was not init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…It has previously been reported that Valsalva retinopathy can occur due to a variety of physical movements [6][7][8][9][10][11][12][13][14][15][16], such as bungee jumping [6][7][8][9][10][11], weight lifting [12,13], push-ups [14,15], and aerobics [16]. However, and to the best of our knowledge, there had only been one published report of Valsalva retinopathy caused by performing a handstand [5].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that Valsalva retinopathy can occur due to a variety of physical movements [6][7][8][9][10][11][12][13][14][15][16], such as bungee jumping [6][7][8][9][10][11], weight lifting [12,13], push-ups [14,15], and aerobics [16]. However, and to the best of our knowledge, there had only been one published report of Valsalva retinopathy caused by performing a handstand [5].…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] In the recent years, several case reports have documented a variety of ocular injuries caused by bungee jumping. [ 3 4 5 6 7 8 9 ] In most of these cases, the patients had an initial presentation of blurred vision, whose severity ranged from mildly reduced visual acuity of 20/30 to dramatically deteriorated vision of counting fingers. [ 6 7 8 10 ] Most of them had favorable visual outcomes under conservative treatment and regular follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…suggested the effect of the Valsalva phenomenon on the eye which should be considered to be another pathophysiological factor causing ocular injuries in bungee jumpers. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…23 Intravenous pressures can rise to more than 100 mm Hg following a rapid-3G deceleration during a bungee jump, and this may result in intraocular haemorrhages. 3 Tractional retinal detachment and its related complications can also arise from the mechanical effect of the gravitational force on vitreous movement. Traumatic ocular injury has also been inflicted by the bungee cord itself.…”
Section: Traumatic Eye Injuriesmentioning
confidence: 99%